KINERJA KAMBING SABURAI YANG DIPELIHARA PETERNAK DI DESA GISTING ATAS KECAMATAN GISTING KABUPATEN TANGGAMUS - Ananta Maulana Fikri; Kusuma Adhianto; Ali Husni; Arif Qisthon (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
The aim of this research was to determine the performance of Saburai goats reared by farmer in Gisting Atas Village, Gisting District, Tanggamus Regency. These research was conducted in June until August 2019 in Saburai goat breeding group at Gisting Atas Village, Gisting District, Tanggamus Regency, Lampung Province. The research used 14 farmers as respondents and their Saburai goats with various age levels, namely at kid, young goat, and dam. The research method used was direct interviews and observations in the field which include collecting farmer profile data, while livestock performance data was observed using data recording of the animal. The data was analyzed by descriptive analysis. The results showed that 100% of farmers motivation was to increase their income. Each farmer had 10 tail of goat in average. The average performance of goats were kidding intervals of 310.43±49.70 days, litter size of 1.88±0.40 tails, postpartum oestrus of 61.58±9.72 days, postpartum mating of 149.11±51,19 days, birth weight of 2.83±0.11 kg, weaning weight of 11.28 ±1.36 kg, and yearling weight of 25.98±2.93 kg. The Conclusion of this research was that the performance of Saburai goats that are kept by farmers has decreased if compared with performance of many years before current research. Keywords : Gisting Atas, Performance, Saburai Goat, Tanggamus Regency.